Argonautas y caminantes - López, Augusto Serrano (Universidad Nacional Autónoma De Honduras, 2012)
DOI: http://dx.doi.org/10.5377/pdac.v1i0.834 Población y Desarrollo - Argonautas y Caminantes Vol.1 2003 11-12